A millennium of cold and humid climate decreased carbon accumulation in the subtropical monsoon peatland - Bin Liu; Hanxiang Liu; Ying Wang; Zicheng Yu; Yuwen Fu; Zhengyu Xia; Chengyu Miao; Jia Jia (Communications Earth & Environment)
Abstract In the subtropical monsoon region of China, the climate differs from that of most northern peatlands, where many peatlands have developed in mountainous areas. However, it remains unclear how the carbon dynamics of these subtropical peatlands respond to climate change. Here, we reconstructed the net carbon fluxes of a typical mountainous peatland in Tianmu Mountain, eastern China, over the past thousand years. Humidity and winter temperature are two important climatic factors influencing carbon accumulation (Deviance explained 77.2%) and drought promotes Qianmutian peatland initial development. Despite the decline in carbon accumulation over the last millennium, the peatland’s net carbon balance remains in a ‘carbon sink’ state. This suggests that the risk of carbon release from the peatland carbon pool under natural climate change conditions is not substantial in the subtropical monsoon area.